Pengenalan Profesi atau Cita-Cita Oleh Siswa/Siswi Kelas IV dan VI di SDN Jatisari - Egita Maya Rohimah; Li' izzah Diyanita Manzil; Revita Putri Ma'rifah; Amrina Rosyadah; Nur Anisa; Nendy Velcita Ayu Ramadhani; Isvi Unaizahroya; Ngizatul Afifah; Agung Nugroho Puspito (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
This community service activity aims to improve professional understanding and learning motivation of elementary school students through an inspirational classroom program with the theme ”Introduction to Professions and Aspirations.“ This program was implemented at SDN Jatisari, Wringin District, Bondowoso Regency, on September 4, 2025, teaching 45 fourth and sixth grade students. The method used was an active learning approach through lectures, interactive activities, inspirational video screenings, and career introductions. The evaluation of this activity used a pre-test design, participatory observation, and student assessment. The results showed an increase in the average understanding of students from 40% in the pre-test to 92% in the post-test. The goal was to create a fun learning atmosphere and encourage active student participation. From this community service activity, students became more enthusiastic about asking questions and connecting their aspirations with their daily learning activities. Additionally, teachers at SDN Jatisari, Wringin District, Bondowoso Regency stated that this program had a positive impact on students' enthusiasm for learning and character development, particularly in boosting their confidence and awareness of the benefits of learning. The program also strengthened the relationship between universities and elementary schools in building an inspiring and meaningful educational environment. Inspirational classes can serve as a model for contextual learning in supporting character building and early career planning.